Ruminal Acidosis Caused by Excessive Ingestion of Mango Fruit (Mangifera indica) in Cow - Gomes, Lianna Ghisi; de Faria Júnior, Wilson Gonçalves; Pimentel, Viviane Antunes; Spiller, Paulo Roberto; Ferreira de Paiva, Fernando Weibe; de Paiva, Éverton Pereira (Acta Scientiae Veterinariae, 2019)
Background: Digestive disturbances in ruminants are associated with forage shortages during periods of dry weather. Foods available at this time are generally of poor quality and low digestibility, which makes it necessary to pursue alternative food sources where available. Grain-heavy diets; concentrated rations rich in rapidly fermenting carbohydrates; and whey, tubers and fruits high in starch and glucose, contribute to ruminal acidosis. Here we report a case of ruminal acidosis due to excessive ingestion of the mango fruit (Mangifera indica), "manguita" cultivate, by an adult bovine. Case: In the municipality of Boa Vista, Roraima, during December, a Dutch female bovine adult, weighing approximately 600 kg, was observed showing signs of apathy for two days with diarrhea. The animal had a rumenostomy with flexible cannula in the left paralumbar fossa and was in the final third of gestation. During clinical examination, the animal was in season, and an increase in the volume of the left dorsal region and changes in physiological variables were observed (lightly pale mucosa, capillary filling time of 4 s, heart rate [HR] of 82 beats per min; respiratory rate (f) of 30 moments per min; absence of ruminal movements and rectal temperature [RT] of 39.5°C). Upon removal of the cannula lid, a considerable amount of liquid and a large quantity of mango (Mangifera indica), "manguita" cultivate, were observed. Blood sample and ruminal fluid were collected and ruminal contents weighing approximately 40 kg were evacuated. Physical-chemical analysis of the ruminal liquid (pH = 4.0, brown color, aqueous consistency and characteristic fruit odor) resulted in a diagnosis of ruminal acidosis. Treatment included administration of fluid therapy (Lactate Ringer; 2 mL/kg/h), hepatoprotector (1 mL/20 kg), antimicrobial (Ampicillin Sodium; 10 mg/kg/IV and Sulfadoxine; 30 mg/kg/IV) and non-steroidal anti-inflammatory (Meloxicam; 0.5 mg/kg/IV) drugs, associated with evacuation of ruminal contents, and administration of grass and transfaunation, for three days. Following treatment, the physiological variables and physical-chemical characteristics of the ruminal liquid returned to normal limits (pH = 6.0, greenish brown coloration, aqueous consistency and aromatic normal ruminal liquid odor). By 30 days of initial care, the animal was active and had given birth, with no abnormal changes in physiological variables and physical-chemical characteristics of the ruminal fluid. Discussion: A decrease in food supplies during the dry season forces animals to seek alternative sources of food to meet their needs, as observed in this case study. Intake of a large amount of mango was the cause of ruminal acidosis due to an overabundance of simple sugars. The measures established for the clinical evaluation, diagnostic methods used, collection of blood sample and rumen fluid, and the adopted therapy, administration of fluid therapy, antimicrobial and non-steroidal anti-inflammatory, associated with evacuation of the ruminal content, transfaunation, administered directly to the rumen, were essential to directing the diagnosis and obtaining a fast recovery time for the female bovine. Therefore, it can be concluded the excessive intake of fruit was the primary cause of rumen acidosis, and efficient case management led to observed clinical improvements in the physical-chemical characteristics of the ruminal liquid, with no recurrence of previous clinical signs.